All over the map: An interobserver agreement study of tumor location based on the PI‐RADSv2 sector map. Issue 2 (17th January 2018) - Greer, Matthew D.; Shih, Joanna H.; Barrett, Tristan; Bednarova, Sandra; Kabakus, Ismail; Law, Yan Mee; Shebel, Haytham; Merino, Maria J.; Wood, Bradford J.; Pinto, Peter A.; Choyke, Peter L.; Turkbey, Baris
Abstract : Background: Prostate imaging reporting and data system version 2 (PI‐RADSv2) recommends a sector map for reporting findings of prostate cancer mulitparametric MRI (mpMRI). Anecdotally, radiologists may demonstrate inconsistent reproducibility with this map. Purpose: To evaluate interobserver agreement in defining prostate tumor location on mpMRI using the PI‐RADSv2 sector map. Study Type: Retrospective. Population: Thirty consecutive patients who underwent mpMRI between October, 2013 and March, 2015 and who subsequently underwent prostatectomy with whole‐mount processing. Field Strength: 3T mpMRI with T2 W, diffusion‐weighted imaging (DWI) (apparent diffusion coefficient [ADC] and b‐ 2000), dynamic contrast‐enhanced (DCE). Assessment: Six radiologists (two high, two intermediate, and two low experience) from six institutions participated. Readers were blinded to lesion location and detected up to four lesions as per PI‐RADSv2 guidelines. Readers marked the long‐axis of lesions, saved screen‐shots of each lesion, and then marked the lesion location on the PI‐RADSv2 sector map. Whole‐mount prostatectomy specimens registered to the MRI served as ground truth. Index lesions were defined as the highest grade lesion or largest lesion if grades were equivalent. Statistical Test: Agreement was calculated for the exact, overlap, and proportion of agreement. Results: Readers detected an average of 1.9 lesions per patient (range 1.6–2.3). 96.3% (335/348) of all lesions for all readers were scored PI‐RADS ≥3. Readers defined a median of 2 (range 1–18) sectors per lesion. Agreement for detecting index lesions by screen shots was 83.7% (76.1%–89.9%) vs. 71.0% (63.1–78.3%) overlap agreement on the PI‐RADS sector map ( P < 0.001). Exact agreement for defining sectors of detected index lesions was only 21.2% (95% confidence interval [CI]: 14.4–27.7%) and rose to 49.0% (42.4–55.3%) when overlap was considered. Agreement on defining the same level of disease (ie, apex, mid, base) was 61.4% (95% CI 50.2–71.8%). Data Conclusion: Readers are highly likely to detect the same index lesion on mpMRI, but exhibit poor reproducibility when attempting to define tumor location on the PI‐RADSv2 sector map. The poor agreement of the PI‐RADSv2 sector map raises concerns its utility in clinical practice. Level of Evidence : 3 Technical Efficacy : Stage 2 J. MAGN. RESON. IMAGING 2018;48:482–490.